Study of etiopathogenesis and clinical profile of patients presenting with abnormal uterine bleeding - Yeole, Namrata; Nayak, Arun H.; Mehendale, Madhuri (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: AUB is a common condition affecting 14-25% of women of reproductive age and may have a significant impact on their physical, social, emotional and material quality of life. AUB can occur at any age in various forms and has different modes of presentation. The key to successful clinical management is to recognize or identify the causative factors responsible. Methods: This study was conducted over 100 patients. Patients with complaints of menstrual irregularity between menarche to premenopausal age group were considered. Data about age, parity, menstrual history, obstetric history, medical history, physical examination, thyroid function test, radiological findings and histopathology were collected and studied. Results: Incidence of AUB is more common in 5th decade of life. Menorrhagia is the most common bleeding pattern. It is concluded that DUB is the most common cause of AUB. Among the other organic pathological causes, fibroid is the commonest. Maximum number of apparently normal patients with abnormal uterine bleeding belong to category of sub clinical hypothyroid. Conclusions: Accurate analysis of endometrial sample is the key to effective therapy and rational approach to treatment of women with abnormal uterine bleeding.